Freedom - Franzen, Jonathan (New York : Farrar, Straus and Giroux, 2010)
The idyllic lives of civic-minded environmentalists Patty and Walter Berglund come into question when their son moves in with aggressive Republican neighbors, green lawyer Walter takes a job in the coal industry, and go- getter Patty becomes increasingly unstable and enraged.
Keywords: Middle class families -- Fiction; City and town life -- Minnesota -- Fiction; Husband and wife -- Minnesota -- Fiction; Dysfuntional family -- Fiction